An accurate determination method for cobalt in sage tea and cobalamin: Slotted quartz tube-flame atomic absorption spectrometry after preconcentration with switchable liquid-liquid microextraction using a Schiff base - Yazici, Elif; Firat, Merve; Chormey, Dotse Selali; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2020)
This study reports a stepwise optimization of switchable liquid-liquid microextraction (SLLME) for cobalt determination by flame atomic absorption spectrometry (FAAS) coupled with a slotted quartz tube (SQT). The main purpose of this study was to develop an accurate and sensitive analytical method for cobalt. Extraction method was used to separate and preconcentrate cobalt from sage tea and vitamin B12 samples after complexing with a Schiff base ligand. 107.7 folds enhancement in detection power under the optimum conditions was recorded with respect to direct FAAS. This enhancement correlated to 3.1 mu g/L limit of detection and 10 mu g/L limit of quantification. The SLLME-SQT-FAAS method was linear over a broad concentration range and low % RSD values established high precision for the method. Appreciable percent recovery results (94-108%) obtained from spiked sage sample and from cobalamin also validated the accuracy of the method.
Keywords: Cobalt; Flame atomic absorption spectrometry; Switchable liquid-liquid microextraction; Slotted quartz tube; Experimental design; Schiff base ligand; PHASE MICROEXTRACTION; WATER SAMPLES; SOLVENT; NICKEL; SELENIUM; FOOD; Chemistry; Food Science & Technology; Nutrition & Dietetics